Study on thermal conductivity and viscosity of Al2O3-transformer oil based nanofluid - Singh, Mandeep (My University, 2013)
A nanofluid is the suspension of nanoparticles in a base fluid. Recent experimental investigations about nanofluids promise their better heat transfer performance which is d ue to their improved thermo physical properties like, thermal conductivity and viscosity. In our experimental investigations nanofluids are prepared by using Al2O3 as nanoparticles of different shape (spherical & elongated) and size (20 nm & 40 nm) in the base fluid which is a transformer oil (transol’s). The test samples are prepared by dispersing Al2O3 in to a transformer oil at three different concentrations 0.1%, 0.3% and 0.5%. All the experimental investigations are carried out in temperature range from 200C- 500C. A stable suspension of nanoparticles in transformer oil is prepared by sonicating the sample for 3 hours in Ultra Sonicator. Two important thermophysical properties namely thermal conductivity & viscosity are investigated experimentally for the prepared nanofluid samples. Thermal conductivity of nanotransformer oil is measured by KD2 pro, a thermal property analyzer and viscosity of nanotransformer oil is measured by Brookfield viscometer (LV DV-IIICP). Effect of various parameters like temperature,concentration of nanoparticles, size and shape of nanoparticles in nanofluids have been investigated. The results show that thermal conductivity and viscosity increases with increase in % vol. concentration of nanoparticles. With temperature, thermal conductivity increases and viscosity decreases almost linearly. With increase in size of nanoparticles, it is found that thermalconductivity and viscosity decreases, which is expected due to decrease in nanolayer thickness and interfacial effects. It is also observed that elongated nanoparticles have more thermal conductivity enhancements due to their higher aspect ratio and contact surface area over the spherical nanoparticles. Viscosity also rises with elongated nanoparticles as compared to spherical nanoparticles.
Master of Engineering-Thermal, Dissertation
Keywords: Nanotransformer oil; Thermal conductivity; AL2O3; Viscosity